Enhancing Student Mathematics Performance Through Teaching Quality, Motivation, and Students Self-efficacy - Dramani, Bilson Abdulai; Dissou Arthur, Yarhands (Manunggal Halim Jaya, 2024)
The current study sought to improve student performance in mathematics by focusing on motivation, student self-efficacy, and teaching quality. The study's descriptive correlation design used a questionnaire to gather data from the intended students. With a sample size of 355 students, the study's population consisted of 3139 students pressuring agric, business, general science, and general arts. Respondents from each stratum were chosen using simple random sampling that was stratified and purposeful. An analysis of the hypothesis routes was conducted using Amos' structural equation model (ver. 23). The student's results showed that improving student performance in mathematics was directly impacted by teaching quality, motivation, and student self-efficacy.